Microstructural and mechanical properties of cBN-Si composites prepared from the high pressure infiltration method. (December 2016) - Liu, Yinjuan; He, Duanwei; Wang, Pei; Yan, Xiaozhi; Xu, Chao; Liu, Fangming; Liu, Jin; Hu, Qiwei
Abstract: The grain size dependence of the mechanical properties of cBN-Si composites prepared using the high pressure infiltration method has been investigated. Indentation testing indicates that cBN-Si composites have hardness values of 38–43 GPa, which increase with increasing grain size and are harder than traditional polycrystalline cBN composites (PcBNs). Thermostability analyses display that cBN-Si composites with a grain size of > 9 μm also possess a higher temperature of oxidation, compared to traditional PcBNs, and the thermostability increases with increasing cBN grain size. Fracture toughness tests show that almost no cracks appear on the polished cBN-Si samples when the loading forces are increased to 294 N and the fracture toughness is better than for commercial samples. Scanning electron microscopy illustrates that deformations and close pores occurred easily between coarse BN grains, leading to denser cBN-Si compacts with better mechanical performances. Highlights: Systematically studying the grain size dependence of mechanical properties and microstructure of cBN-Si composites. The cBN-Si compacts are more denser and have better mechanical performances. The uniformity of the overall performance of cBN-Si composites. The cBN-cBN bonds appeared extensively in the sintered samples. The deformation occurred more easily for the coarse grain cBN than the fine-grained cBN at high pressure and temperature.